Tax Incentives for Disabled Employees - Van Orman, Kess Mariel (2024)
Abstract This thesis explores the lived experiences of Human Resources Professionals (HRPs) in Czechia concerning the quota system for employing persons with disabilities, through semi-structured interview questions. The approach to this thesis is based on qualitative research, supported and enhanced by statistical analysis. The information gathered for the qualitative component was based on structured interviews and was designed to gather the experiences and insights of HRPs in navigating the quota system within their organizations. This approach allowed for an understanding of the intricacies and practical implications of the quote system on the daily operations of HRPs. The supporting quantitative analysis included data collected from a wide range of companies to offer a broader view of the system’s impact and effectiveness across the Czech business landscape. The study also situated the Czech experience within a wider international context through a comprehensive literature review, and by comparing the Czech quota system with those in place in other countries in the European Union. Overall, this thesis sought to contribute a more nuanced understanding of disability employment policies than might be provided by only examining the statistics. The intent was to provide valuable insights for policymakers, business leaders, and advocacy groups aiming to enhance employment opportunities for persons with disabilities.